NCOG-37. MICROSTRUCTURAL CEREBELLAR INJURY IS ASSOCIATED WITH PROCESSING SPEED DECLINE IN ADULTS WITH PRIMARY BRAIN TUMORS: IMPLICATIONS FOR COGNITIVE PRESERVATION. (14th November 2022) - Salans, Mia; Karunamuni, Roshan; Unnikrishnan, Soumya; Qian, Alex; Connor, Michael; Gudipati, Suma; Yip, Anthony; Huynh-Le, Minh-Phuong; Tibbs, Michelle; Reyes, Anny; Stasenko, Alena; Schadler, Adam; et al.
Abstract: PURPOSE: We investigated associations between imaging biomarkers of cerebellar injury and neurocognitive function among primary brain tumor patients receiving partial brain radiotherapy (RT). METHODS: On a prospective trial, 65 patients underwent volumetric brain MRI, diffusion tensor imaging, and memory, executive function, language, attention, and processing speed (PS) assessment pre-, 3, 6, and 12 months post-RT. Delis-Kaplan Executive Function System Trail Making [DKEFS-TM] Visual Scanning and Number and Letter Sequencing and Wechsler-Adult Intelligence Scale-IV [WAIS] Coding subtests evaluated PS. Cerebellar regions of interest (ROIs) were autosegmented, including cortex and white matter (WM). Supratentorial cortical and WM structures subserving the above cognitive domains were also autosegmented. Supratentorial PS-associated ROIs included the posterior, mid-posterior, central, mid-anterior, and anterior corpus callosum along with the bilateral intrahemispheric WM. Volume (cm 3 ) was measured in all ROIs at each timepoint. Diffusion biomarkers (fractional anisotropy [FA] and mean diffusivity [MD]) were measured in all WM structures at each timepoint. Linear mixed-effects models assessed cerebellar biomarkers as predictors of neurocognitive scores. If found to be associated, cerebellar biomarkers were subsequently evaluated as predictors of cognitive scores controlling for domain-specific supratentorial ROI biomarkers. RESULTS: Left (p=0.04) and right (p< 0.001) cerebellar WM volume declined over time. Cerebellar biomarkers were not associated with memory, executive function, or language. Left cerebellar cortex atrophy correlated with worse DKEFS-TM Number (p=0.01) and Letter (p=0.01) Sequencing scores. Right cerebellar cortex atrophy correlated with worse DKEFS-TM Visual Scanning (p=0.02) and Number (p=0.03) and Letter (p=0.02) Sequencing scores. Greater right cerebellar WM MD correlated with worse DKFS-TM Visual Scanning performance (p=0.03). These associations remained significant after controlling for corpus callosum and intrahemispheric WM injury biomarkers. CONCLUSION: Biomarkers of cerebellar injury correlated with worse post-RT PS, independent of corpus callosum and intrahemispheric WM damage. Cerebellar dose avoidance may preserve PS.